2013
DOI: 10.1186/1471-2407-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of erythropoietin in renal cell carcinoma

Abstract: One of the molecules regulated by the transcription factor, hypoxia inducible factor (HIF), is the hypoxia-responsive hematopoietic factor, erythropoietin (EPO). This may have relevance to the development of renal cell carcinoma (RCC), where mutations of the von Hippel-Lindau (VHL) gene are major risk factors for the development of familial and sporadic RCC. VHL mutations up-regulate and stabilize HIF, which in turn activates many downstream molecules, including EPO, that are known to promote angiogenesis, dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 87 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…Although the upregulation of Ki‐67 expression is associated with neck metastasis, recurrence, and poor survival, some studies report a lack of association between Ki‐67 expression and survival . The hypoxia‐responsive hematopoietic factor, erythropoietin, is one of the molecules regulated by HIF . Erythropoietin and EPOR expression are associated with poor prognosis in patients with cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Although the upregulation of Ki‐67 expression is associated with neck metastasis, recurrence, and poor survival, some studies report a lack of association between Ki‐67 expression and survival . The hypoxia‐responsive hematopoietic factor, erythropoietin, is one of the molecules regulated by HIF . Erythropoietin and EPOR expression are associated with poor prognosis in patients with cancer .…”
Section: Discussionmentioning
confidence: 99%
“…EPO is widely used to treat tumor-related anemia, however, the effect of EPO on RCC has not been well delineated (19). Several studies observed that exogenous recombinant human EPO inhibits cancer progression, however, other studies indicated that it promotes cancer progression (20)(21)(22).…”
Section: Fbp1 Expression --------------------------------------------mentioning
confidence: 99%
“…cancers including hepatocellular carcinoma 42,43 . EPO may also stimulate epithelialmesenchymal transition (EMT) associated with cancer progression 44 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%